The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1002/bit.20253
|View full text |Cite
|
Sign up to set email alerts
|

Quartz crystal microbalance‐based measurements of shear‐induced senescence in human embryonic kidney cells

Abstract: Fluid shear and other mechanical forces play an important role in the normal biophysical, biochemical, and gene regulatory responses of vertebrate tissue that are reflected in the expression of normal cell differentiation, growth, and function. Despite some promising work reported on the application of the quartz crystal microbalance (QCM) to both prokaryote and eukaryote cells over the last decade, QCM has yet to be successfully applied to cells in culture under conditions of flow-induced shear. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…This is in good agreement with numerous publications describing that shear stress can hamper cell adhesion. [36] Unfortunately, there seems to be only one publication investigating the shear stress on cells caused by a QCM under dynamic conditions, [18] making it difficult to estimate its influence on cell adhesion within this system. Experiments with higher pump speeds (and therefore higher shear stress) resulted in significantly lower cell adhesion, a fact, which supports these assumptions (data not shown) and was also described by Jenkins et al [18] Suppressing Cell Adhesion by Grafting PEG Molecules to the Surface A completely different result was obtained when the gold electrodes were modified with (NH 2 PEG 2000 C 11 S) 2 .…”
Section: Detection Of Cell Adhesion Using Non-modified Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in good agreement with numerous publications describing that shear stress can hamper cell adhesion. [36] Unfortunately, there seems to be only one publication investigating the shear stress on cells caused by a QCM under dynamic conditions, [18] making it difficult to estimate its influence on cell adhesion within this system. Experiments with higher pump speeds (and therefore higher shear stress) resulted in significantly lower cell adhesion, a fact, which supports these assumptions (data not shown) and was also described by Jenkins et al [18] Suppressing Cell Adhesion by Grafting PEG Molecules to the Surface A completely different result was obtained when the gold electrodes were modified with (NH 2 PEG 2000 C 11 S) 2 .…”
Section: Detection Of Cell Adhesion Using Non-modified Sensorsmentioning
confidence: 99%
“…[36] Unfortunately, there seems to be only one publication investigating the shear stress on cells caused by a QCM under dynamic conditions, [18] making it difficult to estimate its influence on cell adhesion within this system. Experiments with higher pump speeds (and therefore higher shear stress) resulted in significantly lower cell adhesion, a fact, which supports these assumptions (data not shown) and was also described by Jenkins et al [18] Suppressing Cell Adhesion by Grafting PEG Molecules to the Surface A completely different result was obtained when the gold electrodes were modified with (NH 2 PEG 2000 C 11 S) 2 . In previous investigations, we could show, that the PEG derivatives we synthesized form self-assembled monolayers on gold surfaces, and can significantly reduce the adsorption of proteins due to steric repulsion of PEG, [5,7] an effect which has extensively been described in the literature.…”
Section: Detection Of Cell Adhesion Using Non-modified Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell layer exhibited periodic, synchronous contractions at a rate of about 1.5 Hz, which was clearly reflected in periodic variations of the resonance frequency and bandwidth, and which could be modulated by stimulating drugs such as isoproterenol. Cell-based studies have also been extended to monitor shear-induced senescence in human embryonic kidney cells in culture under conditions of flow-induced shear (Jenkins et al, 2004b), and vesicle release and retrieval (Cans et al, 2001). In the latter study, increasing potassium concentration in the media was shown to stimulate exocytosis, whilst the endocytosis was spontaneous.…”
Section: Cellular Responses To Exogenous Stimulimentioning
confidence: 99%
“…Of the measurement methods, surface plasmon resonance (SPR) (Baac et al, 2006;Hodin et al, 2007;Jacquemart et al, 2008;Suenaga et al, 2003;Wolf et al, 2005) and quartz crystal microbalance (QCM) (Hodin et al, 2007;Jenkins et al, 2004;Nakano et al, 2007;Rawle et al, 2007;Sota et al, 2002) are very popular. For these measurements, some types of sensor chips are commercially available, although there are in general numerous immobilization methods (Rusmin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%